2020
DOI: 10.5415/apallergy.2020.10.e21
|View full text |Cite
|
Sign up to set email alerts
|

Activation of inflammation and resolution pathways of lipid mediators in synovial fluid from patients with severe rheumatoid arthritis compared with severe osteoarthritis

Abstract: Background: The upregulation of the cyclooxygenase and lipoxygenase pathways of arachidonic acid is thought to be involved in the development of rheumatoid arthritis. Recently, the presence of specialized pro-resolving lipid mediators in synovial tissues from patients with osteoarthritis has been reported. Objective: To clarify the quantitative and qualitative changes in lipid mediators in the synovium of severe rheumatoid arthritis patients, we compared the profiles of lipid mediators in synovial fluid obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Therefore, a comprehensive understanding of the human body measures for proper control of the heightened inflammatory state is encouraged for better treatment modalities. Lipid mediators including AA and its associated metabolites are crucial players in the initiation of the inflammatory response in addition to their role in the process of resolution [57,58]. The resolution of inflammation has been previously considered as a passive process.…”
Section: The Potential Role Of Arachidonic Acid-derived Epoxyeicosatrmentioning
confidence: 99%
“…Therefore, a comprehensive understanding of the human body measures for proper control of the heightened inflammatory state is encouraged for better treatment modalities. Lipid mediators including AA and its associated metabolites are crucial players in the initiation of the inflammatory response in addition to their role in the process of resolution [57,58]. The resolution of inflammation has been previously considered as a passive process.…”
Section: The Potential Role Of Arachidonic Acid-derived Epoxyeicosatrmentioning
confidence: 99%
“…Our previous study indicated that two other SPMs, maresin 1 (MaR1) and resolvin D1 (RvD1), moderated the inflammatory response in RA 10 , 11 . As for protectin D1, Sano found that it was increased in synovial fluid in RA 12 . It is also reported that protectin D1 inhibits secretion of TNF-α, as a pro-inflammatory cytokine that enhances the progression of RA 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The most important of these proteinases consist of two enzyme families, matrix metalloproteinases (MMP) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) [ 15 ]. In addition to pro-inflammatory lipid mediators, several SPM are present in diseased joints [ 3 , 20 ]. Normally, the inflammatory response is self-limiting, but it can become chronic in pathological conditions, such as RA, in which inflammation fails to resolve [ 21 ].…”
Section: Introductionmentioning
confidence: 99%